MODEL OF DHF DISTRIBUTION IN CITY/REGENCY OF WEST JAVA - STRASSIA, ELSA
Dengue Hemorrhagic Fever (DHF) is a disease caused by the bite of Aedes aegypti and Aedes albopictus mosquitoes. DHF causes death if not treated properly. Until July 2020, West Java was the province with the highest number of dengue patients in Indonesia. Therefore, it is necessary to make prevention efforts in cities/districts in West Java which have the potential to have a high number of DHF sufferers. In this study, the application of the Generalized Linear Model (GLM) was used to observe the distribution pattern of DHF cases in West Java and cluster analysis was used to classify DHF cases in cities/districts of West Java. From 27 cities/regencies of West Java, only 5 cities/regencies that can be followed up to implement GLM are Cimahi City, West Bandung Regency, Kuningan Regency, Sumedang Regency and Subang Regency. However, this model is not good in modeling cases of DHF in the city/regency of West Java because it provides a fairly large MSE and RMSE. From five methods used to group dengue cases, average linkage is the best method because it has the highest average silhouette coefficient and Dunn index values. This method is used to determine groups of low, moderate and high dengue cases. The group of cities/districts that have the highest DHF cases is Bandung City and Bogor Regency, which is characterized by the average weekly DHF case often occupying the highest score compared to other city/regency groups.